A novel murine model of autoimmune dysautonomia by α3 nicotinic acetylcholine receptor immunization - Yamakawa, Makoto; Nakane, Shunya; Ihara, Eikichi; Tawara, Nozomu; Ikeda, Hiroko; Igarashi, Yoko; Komohara, Yoshihiro; Takamatsu, Koutaro; Ikeda, Tokunori; Tomita, Yusuke; Murai, Shoichi; Ando, Yukio; et al. (Frontiers in Neuroscience, 2022)
We aimed to establish a novel murine model of autoimmune autonomic ganglionopathy (AAG), which represents autoimmune dysautonomia, associated with MHC class II to understand its pathomechanism and the pathogenicity of nicotinic acetylcholine receptor (nAChR) antibodies. The amino acid sequence of the mouse nAChRα3 protein was analyzed using an epitope prediction tool to predict the possible MHC class II binding mouse nAChRα3 peptides. We focused on two nAChRα3 peptides in the extracellular region, and experimental AAG (EAAG) was induced by immunization of C57BL/6 mice with these two different peptides. EAAG mice were examined both physiologically and histologically. Mice with EAAG generated nAChRα3 antibodies and exhibited autonomic dysfunction, including reduced heart rate, excessive fluctuations in systolic blood pressure, and intestinal transit slowing. Additionally, we observed skin lesions, such as alopecia and skin ulcers, in immunized mice. Neuronal cell density in the sympathetic cervical ganglia in immunized mice was significantly lower than that in control mice at the light microscopic level. We interpreted that active immunization of mice with nAChRα3 peptides causes autonomic dysfunction similar to human AAG induced by an antibody-mediated mechanism. We suggested a mechanism by which different HLA class II molecules might preferentially affect the nAChR-specific immune response, thus controlling diversification of the autoantibody response. Our novel murine model mimics AAG in humans and provides a useful tool to investigate its pathomechanism.